MORAL VALUES AND INTRINSIC ELEMENTS DEPICTED IN NOVEL ENTITLED THE LAND OF FIVE TOWERS BY AHMAD FUADI - Nur'asiyah Nur'asiyah; Rusman Roni; Baginda Simaibang (ELTE Journal (English Languange Teaching and Education), 2020)
This study is entitled “Moral Values and Intrinsic Elements Depicted in Novel Entitled The Land of Five Towers By Ahmad Fuadi”.Data were collected by using the novel. Data were analyzed by detailing intrinsic elements, moral values, and the theoretical implications for English Language Teaching. The findings of this research explained some interesting things about this novel. First, it was about how Alif’s life at present, his life in Bukittinggi and Pondok Madani (PM) boarding school, Alif met with his friends at PM, and they were together to make their dreams come true. This information made this novel more interesting. Second, there were four moral values found in this novel, 1) responsibility, 2) sincerity, 3) patience, and 4) yearning. Third, this novel could be used as a tool for teachers to teach about dreams, motivations and inspirations, success tips, self-preservation in High Schools. The conclusion sug